IMPLEMENTASI KEBIJAKAN DANA DESA DALAM MENINGKATAN PEMBANGUNAN DI DESA WUKIRSARI, KABUPATEN SLEMAN - Fransisca Winarni; Pandhu Yuanjaya (Yogyakarta State University, 2016)
This study aims to determine the implementation of the Village Funds as an effort to increase rural development in the village Wukirsari Cangkringan Sleman. The research approach used in this research was descriptive qualitative. Techniques of data retrieval were done through observation, interview, and review of documentation. Data analysis technique used interactive analysis techniques adopted from Mills and Huberman. Rnenunjukkan research results that the policy implementation using village funds under Regulation 60 Year 2016 Wukirsari village crushing implemented. The result of the development of the use of village funds was used for infrastruscture development. The success of the policy implementation due to factors of good communication, the resources both human capacity and adequate funding, clear and coordinated bureaucratic structure, and good commitment and integrated bureaucratic disposition to the success of rural development in Wukirsari.Keyword: Village Funds, Rural Development, Policy Implementation